2016
DOI: 10.1016/j.ccell.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

LYN Kinase in the Tumor Microenvironment Is Essential for the Progression of Chronic Lymphocytic Leukemia

Abstract: Survival of chronic lymphocytic leukemia (CLL) cells strictly depends on the support of an appropriate tumor microenvironment. Here, we demonstrate that LYN kinase is essential for CLL progression. Lyn deficiency results in a significantly reduced CLL burden in vivo. Loss of Lyn within leukemic cells reduces B cell receptor (BCR) signaling including BTK phosphorylation, but surprisingly does not affect leukemic cell expansion. Instead, syngeneic CLL transplantation of CLL cells into Lyn- or Btk-deficient recip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 72 publications
3
73
0
Order By: Relevance
“…As chemokine secretion may entail a selection advantage for malignant B cells in vivo, its dependence on BTK activity could favour mutations at cysteine 481 in clinically acquired ibrutinib resistance. Our demonstration of maintained chemokine secretion in the presence of ibrutinib owing to the BTK‐C481S mutation reconciles the selection of resistance mutations in malignant B cells exhibiting acquired ibrutinib resistance (Woyach et al , ) with prevalent contributions of accessory cells to the roles of BTK and LYN in CLL pathogenesis (Nguyen et al , ).…”
supporting
confidence: 78%
“…As chemokine secretion may entail a selection advantage for malignant B cells in vivo, its dependence on BTK activity could favour mutations at cysteine 481 in clinically acquired ibrutinib resistance. Our demonstration of maintained chemokine secretion in the presence of ibrutinib owing to the BTK‐C481S mutation reconciles the selection of resistance mutations in malignant B cells exhibiting acquired ibrutinib resistance (Woyach et al , ) with prevalent contributions of accessory cells to the roles of BTK and LYN in CLL pathogenesis (Nguyen et al , ).…”
supporting
confidence: 78%
“…In a murine model of chronic lymphocytic leukemia (CLL), transplantation of CLL cells into mice deficient for the Lyn kinase or Bruton's tyrosine kinase (BTK) led to a decelerated leukemia progression and prolonged survival, suggesting that Lyn and BTK in the BMM are essential for leukemic progression in CLL. Interestingly, Lyn deficiency in macrophages, which exert a 'nursing' function for CLL cells through direct cell-cell contact, were implicated in the observed phenotype (Nguyen et al, 2016) (see poster).…”
Section: Cell Adhesion Molecules and Other Niche Components Involved mentioning
confidence: 99%
“…1 – 4 showed that Lyn can efficiently phosphorylate ROR1 that can be subsequently recognized by c-CBL. ROR1 and Lyn are important regulators of signaling pathways driving chronic lymphocytic leukemia (CLL) 1,8,21,35 and several lymphomas, namely mantle cell lymphoma (MCL) 15 . Both, Lyn and ROR1, have been evaluated as therapeutic targets in these malignancies and the understanding of their mutual cross talk is thus of direct therapeutic relevance.…”
Section: Resultsmentioning
confidence: 99%